Photoswitch dissociation from a G protein-coupled receptor resolved by time-resolved serial crystallography - Hannah Glover; Torben Saßmannshausen; Quentin Bertrand; Matilde Trabuco; Chavdar Slavov; Arianna Bacchin; Fabio Andres; Yasushi Kondo; Robin Stipp; Maximilian Wranik; Georgii Khusainov; Melissa Carrillo; et al. (Nature Communications)
Abstract G protein-coupled receptors (GPCRs) are the largest family of cell surface receptors in humans. The binding and dissociation of ligands tunes the inherent conformational flexibility of these important drug targets towards distinct functional states. Here we show how to trigger and resolve protein-ligand interaction dynamics within the human adenosine A2A receptor. For this, we designed seven photochemical affinity switches derived from the anti-Parkinson’s drug istradefylline. In a rational approach based on UV/Vis spectroscopy, time-resolved absorption spectroscopy, differential scanning fluorimetry and cryo-crystallography, we identified compounds suitable for time-resolved serial crystallography. Our analysis of millisecond-scale dynamics revealed how trans-to-cis isomerization shifts selected istradefylline derivatives within the binding pocket. Depending on the chemical nature of the ligand, interactions between extracellular loops 2 and 3, acting as a lid on the binding pocket, are disrupted and rearrangement of the orthosteric binding pocket is invoked upon ligand dissociation. This innovative approach provides insights into GPCR dynamics at the atomic level, offering potential for developing novel pharmaceuticals.